Absence of meningeal mast cells in the Mitf mutant mouse - Sabaté San José, Alba; Petersen, Petur Henry (Frontiers in Cellular Neuroscience, 2024)
Mast cells (MC) are located in the meninges of the central nervous system (CNS) where they play key roles in the immune response. MC deficient mice are advantageous in delineating the role of MC in the immune response in vivo. Here we illustrate that a mutation in microphthalmia associated transcription factor (Mitf) affects meningeal MC number in a dosage dependent manner. C57BL/6J Mitf null mice lack meningeal MC completely whereas heterozygous mice have on average 25% fewer MC. Mitf heterozygous mice might be a valuable tool to study the role of MC in the meninges.